Derivation of novel naive‐like porcine embryonic stem cells by a reprogramming factor‐assisted strategy. Issue 8 (24th May 2019) - Zhang, Manling; Wang, Chenyu; Jiang, Haibin; Liu, Manling; Yang, Ning; Zhao, Lihua; Hou, Daorong; Jin, Yong; Chen, Qiaoyu; Chen, Yuan; Wang, Junzheng; Dai, Yifan; et al.
ABSTRACT: The establishment of ungulate embryonic stem cells (ESCs) has been notoriously difficult via a conventional approach. We combined a traditional ESC culture method with reprogramming factors to assist the establishment of porcine naive‐like ESCs (nESCs). Pig embryonic fibroblasts were transfected with a tetracycline‐inducible vector carrying 4 classic mouse reprogramming factors, followed by somatic cell nuclear transfer and culturing to the blastocyst stage. Then, the inner cell mass was isolated and seeded in culture medium. The naive‐like ESCs had characteristic verys similar to those of mouse ESCs and showed no signs of altered morphology or differentiation, even after 130 passages. They depended on leukemia inhibitory factor signals for maintenance of pluripotency, and the female cell lines had low expression of the X‐inactive specific transcript gene and no histone H3 lysine 27 trimethylation spot. Notably, the ESCs differentiated into 3 germ layers in vitro and could be induced to undergo directional neural and kidney precursor differentiation under defined conditions, and the ESCs could keep proliferating after doxycycline was removed. nESCs can be established, and the well‐characterized ESC lines will be useful for the research of transgenic pig models for human disease.—Zhang, M., Wang, C., Jiang, H., Liu, M., Yang, N., Zhao, L., Hou, D., Jin, Y., Chen, Q., Chen, Y., Wang, J., Dai, Y., Li, R. Derivation of novel naive‐like porcine embryonic stem cells by a reprogramming factor–assisted strategy. FASEB J. 33, 9350–9361 (2019). www.fasebj.org